The Mass Distribution of Soputan Volcano Based on Gravity Data - Dave Emmanuel Haning; Agus Setyawan; Rina Dwi Indriana (Journal of Physics and Its Applications, 2022)
The gravity method is a passive method based on the density measurement among sediment. This method is usually applied to identify the condition of the earth’s subsurface. Soputan Volcano is located in District Minahasa Tenggara. Soputan Volcano is included in type A Volcano or stratovolcano and it stands at 1783.7 MSL. This research aims to identify the distribution of subsurface mass (sediment density) of Soputan. The data used was Data from satellite GGmPlus and elevation data of ERTM which was corrected to ellipsoid reference. 3D inversion modeling applied Grablox software. The complete value of the Bouguer anomaly obtained was 110 – 162 mGal. The density result obtained from the inversion model was 2.3 g/cm3 to 2.95 g/cm3. The sediment that could be identified was andesite sediment and basalt sediment. Based on that result, the layer arranging Soputan Volcano consists of many variations of mass in each depth grouped into andesite, breccia, basalt, andesite-basaltic, lava, breccia, and tuff.